Enhancement of Shelf-Life of Buffalo Milk Using Hydrogen Peroxide (Research in Agriculture Livestock and Fisheries, 2025)
The research was conducted to weigh the shelf-life and microbial properties in response to adding hydrogen peroxide (H2O2) and its residues in buffalo milk. For this purpose, raw milk was collected from the Bangladesh Agricultural University Dairy Farm and treated with different proportions (%) of H2O2. Organoleptic, chemical, and microbial tests were done to achieve the aim of the work. Incorporation of different levels of hydrogen peroxide can stabilize the physical, chemical, and microbial properties, where 0.16% H2O2 shows better results. For residual effect detection of H2O2, up to 0.12% shows a lower disappearance time after boiling. The results of the experiment indicate that H2O2 can be used as an excellent preservative.Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 07-14